Assembly of tomato fruit cuticles: a cross‐talk between the cutin polyester and cell wall polysaccharides. Issue 3 (10th February 2020) - Philippe, Glenn; Geneix, Nathalie; Petit, Johann; Guillon, Fabienne; Sandt, Christophe; Rothan, Christophe; Lahaye, Marc; Marion, Didier; Bakan, Bénédicte
Summary: The cuticle is an essential and ubiquitous biological polymer composite covering aerial plant organs, whose structural component is the cutin polyester entangled with cell wall polysaccharides. The nature of the cutin‐embedded polysaccharides (CEPs) and their association with cutin polyester are still unresolved Using tomato fruit as a model, chemical and enzymatic pretreatments combined with biochemical and biophysical methods were developed to compare the fine structure of CEPs with that of the noncutinized polysaccharides (NCPs). In addition, we used tomato fruits from cutin‐deficient transgenic lines cus1 ( cutin synthase 1 ) to study the impact of cutin polymerization on the fine structure of CEPs. Cutin‐embedded polysaccharides exhibit specific structural features including a high degree of esterification (i.e. methylation and acetylation), a low ramification of rhamnogalacturonan (RGI), and a high crystallinity of cellulose. In addition to decreasing cutin deposition and polymerization, cus1 silencing induced a specific modification of CEPs, especially on pectin content, while NCPs were not affected. This new evidence of the structural specificities of CEPs and of the cross‐talk between cutin polymerization and polysaccharides provides new hypotheses concerning the formation of these complex lipopolysaccharide edifices.